Subsídios para repensar o sistema federal de planejamento - Ronaldo Coutinho Garcia; José Celso Cardoso Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This reflection is part of a larger project whose goal is to produce suggestions for reshaping the planning process of the federal government and, further, offering elements of methodological and organizational nature for the preparation of the Multiyear Plan (PPA) 2016-2019. The idea of preparing federal subsidies to rethink the planning system is motivated by the need to reform it in depth, which is intended to show evident. But mostly, the technopolitical feasibility of undertaking such reform as critical resources required to carry it forward are almost all under the control of the Federal Executive Branch. The main difficulty for the task relates to achieve allocate the time of the main leading to this task. Ie, able to make dominant understanding that the time spent with the reform is not lost time or dedicated the smallest thing, but time applied in the preparation of the structural conditions to make better and faster later on. In other words, a time taken to produce longer.
Keywords: H8; H80; 330; state; government planning; PPA 2016-2019; Brazil